Skin Cancer Prevention Behaviors among Northeast Florida College Students - Julie W. Merten (University of North Florida, 2015)
Skin cancer is the most common cancer in the United States with over three million people diagnosed annually. Melanoma rates in the past 40 years have increased 800% in women and 400% in men under the age of 39. Ultraviolet radiation is directly linked with the development of skin cancer; moreover, young adults are the most active age group engaging in risky UV exposure. This study seeks to extend scientific understanding of skin cancer prevention behaviors among college students. A convenience sample of 747 college students were surveyed at a midsized Northeast Florida university using the National Cancer Institute core skin cancer prevention questionnaire. The majority of students did not regularly practice sun safety behaviors. Women were more likely to use sunscreen than men; however, women spent more time in the sun for tanning purposes (p < .05). Over half of the participants (53%) spent more than two hours outside during the previous summer, and 65% of participants reported having one or more sunburns in the previous year. Insufficient skin cancer prevention behaviors were apparent. Despite widespread educational efforts to reduce skin cancer, college students receive large amounts of intentional and unintentional exposure to UV radiation, either from the sun, or indoor tanning.